(untitled) (AYUSHDHARA, 2025)
Melanocyte degeneration, which results from the autoimmune loss of melanocytes, is associated with vitiligo, an acquired macular de-pigmentation disorder. Because of the disease’s similar appearance, this vitiligo can be compared to Shwitra in Ayurveda classics. Shwitra is referred to as Kushta Roga Chikitsa in ancient Ayurvedic texts, particularly the Charaka Samhita. Methodology: Shodhana and Shamana Chikitsa were used to treat a 32-year-old male patient who complained of white, discoloured areas on his nape of neck, trunk, and around his knee and elbow joints. Results: After treatment, individual criteria were assessed using the subjective criteria and VASI scoring system, and the patient showed encouraging results in this study. Discussion: After the patient received treatment with Shamana Aushadis and Shodhana, the white, discolored spots changed to a pinkish hue before returning to their natural skin tone. The subjective criteria for patients showed a 9% improvement, and the VASI score reduced from 3.5 to 0.4. Conclusion: The current case study confirmed the effectiveness of Ayurvedic medication in treating Shwitra.